Stock photos of the Medford/Somerville campus, including the MIDI lab in Halligan Hall, Aidekman Arts Center, the front of Cousens Gym and the athletic fields. Photo 039 - Schutzengel, Aaron (Tufts Archival Research Center, 2008)
Stock photos of the Medford/Somerville campus, including the MIDI lab in Halligan Hall, Aidekman Arts Center, the front of Cousens Gym and the athletic fields.